Public relations : writing and media techniques - Wilcox, Dennis L., ....-; Reber, Bryan H., ....- (New Jersey : Pearson Education, 2013)
Public Relations Writing and Media Techniques is the most comprehensive and up-to-date public relations writing text available. With real-world examples of award-winning work by PR professionals, this new edition continues to help students master the many techniques needed to reach a variety of audiences in today's digital age. The text thoroughly integrates new communication technologies - the Internet, Webcasting, etc. - and shows students the many techniques currently in use to reach a variety of audiences. Clearly written and well-organized, this book emphasizes the nuts and bolts of writing, producing, and distributing public relations materials through traditional and social media. The author provides step-by-step procedures illustrated by examples from actual campaigns to engage today's students. This text also serves as an invaluable resource for public relations practitioners in the field.
Includes index.
Keywords: Public relations -- Authorship -- United States; Public relations -- United States; Public relations